English Teachers’ Assessment Practices in Inclusive Elementary School Classrooms - I Gede Angga Pebriawan; Ni Luh Putu Eka Sulistia Dewi; A.A Gede Yudha Paramartha (MAN 4 Kota Pekanbaru, 2026)
English language learning in inclusive elementary school classrooms involves students with diverse abilities and learning needs, requiring assessment practices that accommodate their characteristics. However, teachers still face various challenges in implementing assessments that address the needs of all students, while studies specifically examining assessment practices in inclusive elementary school English classrooms remain limited. This study aimed to analyze the implementation of assessment and the challenges faced by teachers in inclusive English language learning. This study employed a qualitative approach with a single case study design. The participants consisted of one English teacher and 28 second-grade elementary school students. Data were collected through document analysis, classroom observation, and interviews, and were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that assessment was implemented through diagnostic, formative, and summative assessments, with adaptations provided for students with special needs. Teachers faced challenges related to the diversity of students’ abilities, limited instructional time, and the absence of structured differentiated assessment guidelines. This study concludes that assessment in inclusive classrooms is implemented adaptively to accommodate diverse learning needs. These findings imply the need to develop systematic differentiated assessment guidelines and to enhance support and professional training for teachers.